2022
DOI: 10.1021/jacs.1c11699
|View full text |Cite
|
Sign up to set email alerts
|

Highly Phosphorescent Planar Chirality by Bridging Two Square-Planar Platinum(II) Complexes: Chirality Induction and Circularly Polarized Luminescence

Abstract: Chiral organometallic complexes have demonstrated many potential and practical applications. However, building metal-induced chirality for square-planar complexes still remains a big challenge, because their 2D planar molecular structures are usually superimposable on their mirror images. Herein, we report a straightforward and efficient way to achieve a novel kind of planar chirality by constructing 3D double-layer molecular structures. When the achiral ligand 1,3,4-oxadiazole-2-thiol (OXT) was used to bridge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 88 publications
2
47
0
2
Order By: Relevance
“…[1][2][3] The current research has revealed the importance of developing efficient chiral luminescent materials that enable circularly polarized luminescence (CPL) to produce high-performance CP-OLEDs. [4][5][6][7] Generally, the performance standard of the circularly polarized photoluminescence (CPPL) or circularly polarized electroluminescence (CPEL) is characterized by the dissymmetry factor (g PL or g EL ) defined as g = 2 × ΔI/I = 2 × (I L − I R )/(I L + I R ). For example, Meijer et al first obtained CPEL with g EL factor around 10 −3 by using a chiral-substituted poly(p-phenylenevinylene) derivative as emitter.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The current research has revealed the importance of developing efficient chiral luminescent materials that enable circularly polarized luminescence (CPL) to produce high-performance CP-OLEDs. [4][5][6][7] Generally, the performance standard of the circularly polarized photoluminescence (CPPL) or circularly polarized electroluminescence (CPEL) is characterized by the dissymmetry factor (g PL or g EL ) defined as g = 2 × ΔI/I = 2 × (I L − I R )/(I L + I R ). For example, Meijer et al first obtained CPEL with g EL factor around 10 −3 by using a chiral-substituted poly(p-phenylenevinylene) derivative as emitter.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has been commonly utilized in supramolecular, polymer, 43−51 and coordination chemistry, including platinum complexes. 52,53 Recently, planar chirality and helicity inductions of Pt(II) complexes for CPP emitters have been using axial 26 and point chirality. 23 In this study, we demonstrated the helical induction of d-π-conjugated iminopyrrolyl 54−57 Pt(II) complex 1 by the point chirality of 1,2-diaminocyclohexane (Figure 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…35 However, such systems will inevitably suffer from severe inner-filter effects. We have been focusing on manipulating the excited state properties of organic chromophores by supramolecular complexation or chemical tuning of sensitizer structures, 27,31,[36][37][38][39][40][41] and achieved efficient TTA-UC in dilute solutions. 27 On the other hand, boron-dipyrromethene (bodipy), a versatile chromophore with strong visible light absorption, high fluorescence quantum yields and photostability, has been widely used to manipulate the excited states of different metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…35 However, such systems will inevitably suffer from severe inner-filter effects. We have been focusing on manipulating the excited state properties of organic chromophores by supramolecular complexation or chemical tuning of sensitizer structures, 27,31,36–41 and achieved efficient TTA-UC in dilute solutions. 27…”
Section: Introductionmentioning
confidence: 99%